Deteksi Telur Cacing Trichuris trichiura pada Tinja Anak Usia 5-8 Tahun di Jalan Utama Bakaran Batu Kecamatan Batang Kuis Kabupaten Deli Serdang - Indri Rizki Rahmasari; Meida Nugrahalia; Sartini Sartini (Universitas Medan Area, 2022)
Trichuris trichiura is an intestinal nematode commonly called whipworm or whipworm, this worm is relatively often found in humans, T. trichiura infection often occurs in the tropics. This study aims to determine whether there are eggs of T. trichiura worms in the feces of children aged 5-8 years on Main Street Bakaran Batu, Batang Kuis District, Deli Serdang Regency. The research sample was the feces of children aged 5-8 years Main Street Bakaran Batu, Batang Kuis District, Deli Serdang Regency with a sample of 31 children. Qualitative examination of worm eggs. The method used is the direct slide method for rapid examination with the solution used in this study is 2% eosin. The results of this study indicate that with a sample of 31 children aged 5-8 years on Main Street Bakaran Batu, Batang Kuis District, Deli Serdang Regency, there were 5 samples that were positively infected with T. trichiura and as many as 26 children were negatively infected with T. trichiura. It is hoped that infected children will continue to take medicine regularly, maintain cleanliness and have parental supervision